Research of efficiency of water purification-exchange resin from iron compounds using modified filter media - Gomel, Nikolai; Tverdokhlib, Mariia (Eastern-European Journal of Enterprise Technologies, 2016)
Recently, the modified media have become widely used in the processes of iron removal from water. These media are based on the natural granular material with a catalytically-active surface layer, which promotes a more efficient oxidation of iron ions. However, their application raises some problems associated with restoring their oxidative capacity, reliability and duration of use. The paper presents the results of removal of iron ions from water by catalytic oxidation. The method of modifying the filter medium for iron removal from water is developed. The efficiency of iron oxidation with the zeolite and cation-exchange resins modified with iron and manganese compounds is evaluated. It is shown that the modified zeolite is ineffective compared to the modified cation-exchange resin Dowex Mac-3. The manganese-modified cation-exchange resin provides efficient removal of iron ions from water. The iron removal degree was initially 97 % and then gradually decreased to 86 %. The iron concentration in the treated water did not exceed 0.3 mg/dm3. When using the iron-modified cation-exchange resin, the iron concentration decreased from 15 to 0.1–0.2 mg/dm3. The iron removal degree was more than 99 % over a long time. It is found that efficient iron oxidation in water occurs in the presence of sufficient oxygen, that is pre-aeration is required. The drawback of the proposed modified media is a slight loss of oxidative capacity after filter washing.